Artificial intelligence and the medical physics profession - A Swedish perspective. (August 2021) - Andersson, Jonas; Nyholm, Tufve; Ceberg, Crister; Almén, Anja; Bernhardt, Peter; Fransson, Annette; Olsson, Lars E.
Highlights: Swedish survey respondents believed that AI isn't a risk to their practice and career. Most respondents believed that AI will change the practice of medical physics. Respondents were largely positive to the inclusion of AI in educational programmes. Respondents' self-assessed knowledge of, and preparedness for, AI was generally low. Abstract: Background: There is a continuous and dynamic discussion on artificial intelligence (AI) in present-day society. AI is expected to impact on healthcare processes and could contribute to a more sustainable use of resources allocated to healthcare in the future. The aim for this work was to establish a foundation for a Swedish perspective on the potential effect of AI on the medical physics profession. Materials and methods: We designed a survey to gauge viewpoints regarding AI in the Swedish medical physics community. Based on the survey results and present-day situation in Sweden, a SWOT analysis was performed on the implications of AI for the medical physics profession. Results: Out of 411 survey recipients, 163 responded (40%). The Swedish medical physicists with a professional license believed (90%) that AI would change the practice of medical physics but did not foresee (81%) that AI would pose a risk to their practice and career. The respondents were largely positive to the inclusion of AI in educational programmes. According to self-assessment, the respondents' knowledge of and workplace preparedness for AI was generally low. Conclusions: From the survey and SWOT analysis we conclude that AI will change the medical physics profession and that there are opportunities for the profession associated with the adoption of AI in healthcare. To overcome the weakness of limited AI knowledge, potentially threatening the role of medical physicists, and build upon the strong position in Swedish healthcare, medical physics education and training should include learning objectives on AI.